Simulation calculation of the effects of seal face width on mechanical seal performance. Issue 1 (January 2020) - Wei, Long; Fang, Guifang; Zhang, Penggao
Abstract: In order to research and master the effects of seal face width on mechanical seal performance, based on the fractal models of average temperature, friction coefficient and leakage rate of seal faces, the influencing factors of seal face width on mechanical seal performance were analyzed by simulation calculation. The calculation results show that the average temperature of seal faces increased approximately linearly, the friction coefficient and leakage rate of seal faces decreased with the increasing seal face width. The decrease amplitudes of friction coefficient and leakage rate became smaller with the increasing seal face width. The effect degrees of seal face width on friction coefficient and leakage rate increased with the increasing sealed fluid pressure. The change of seal face width has little effect on leakage rate when the sealed fluid pressure was low.